2018
DOI: 10.1038/s41395-018-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower Relative Contribution of Positive Family History to Colorectal Cancer Risk with Increasing Age: A Systematic Review and Meta-Analysis of 9.28 Million Individuals

Abstract: The increase in relative risk of CRC attributed to family history was found to be higher in younger individuals. Family history of CRC could be assigned a higher score for younger subjects in CRC risk prediction algorithms. Future studies should examine if such approach may improve their predictive capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…We showed in this systematic review and metaanalysis that the risk of developing CRC in individuals with a FH of CRC is lower than previously reported, especially according to cohort studies. 4,[79][80][81] RRs at least doubled for individuals having at least 1 FDR with CRC based on case-control studies, and almost tripled for those with at least 2 FDRs with CRC and with a FDR diagnosed with CRC before the age of 50 years. Moreover, AR estimates showed that the risk of developing CRC between 40 and 50 years was low and gradually increased at the age of 50, providing rationale for surveillance recommendations from this age onward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed in this systematic review and metaanalysis that the risk of developing CRC in individuals with a FH of CRC is lower than previously reported, especially according to cohort studies. 4,[79][80][81] RRs at least doubled for individuals having at least 1 FDR with CRC based on case-control studies, and almost tripled for those with at least 2 FDRs with CRC and with a FDR diagnosed with CRC before the age of 50 years. Moreover, AR estimates showed that the risk of developing CRC between 40 and 50 years was low and gradually increased at the age of 50, providing rationale for surveillance recommendations from this age onward.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] A more recent meta-analysis showed lower RR estimates (RR, 1.76; 95% CI, 1.57-1.97). 4 However, these previously published meta-analyses had some drawbacks and limitations: summary estimates consisted of both case-control and cohort studies, none of the studies except the study by Butterworth et al 79 addressed ARs, and the role of the inclusion of individuals with Lynch syndrome was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta‐analyses have reported that stomach, colorectal, liver, pancreas, lung and breast cancers with FH of concordant cancer were associated with an increased risk compared to those without FH. In contrast, prostate cancer with FH of prostate cancer was not associated with an increased risk .…”
Section: Discussionmentioning
confidence: 97%
“…A recent meta-analysis showed that a family history of CRC increased risk of CRC by 3.3 times in young individuals aged < 40 years. 23 Finally, we could not investigate the agespecific risk of NAA or ACRN in detail among individuals aged ≥ 66 years because the sample size of the age group was relatively small. Therefore, extrapolating our results to ages 66 years or older should be done with caution.…”
Section: Discussionmentioning
confidence: 99%